1993
DOI: 10.5935/0305-7518.19930011
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Leprosy

Abstract: From the earliest reports of what has since become the pandemic of human immunodefi ciency virus (HIV) infection, a close association between HIV infection and a previously un common mycobacterial disease-that due to infection with Mycobacterium avium complex (MAC)-was evident. 1 Then and since, clinically significant disease due to MAC is restricted to HIV-positive people in industrialized countries. Later it was realized that M. tuberculosis is associated with HIV infection to the extent that, in sub-Saharan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 7 publications
(8 reference statements)
3
27
0
5
Order By: Relevance
“…It is advisable to postpone pregnancy temporarily during post-therapy period if there is evidence of reaction, relapse, or neuritis. 22,23 Unlike in tuberculosis, HIV disease has not had a significant impact on the clinical course of treated and untreated leprosy. However, it has been reported that the neuritis in co-infected people can be more severe and the reversal reaction may be more frequent after therapy.…”
Section: Hansen's Disease and Pregnancy 2021mentioning
confidence: 95%
“…It is advisable to postpone pregnancy temporarily during post-therapy period if there is evidence of reaction, relapse, or neuritis. 22,23 Unlike in tuberculosis, HIV disease has not had a significant impact on the clinical course of treated and untreated leprosy. However, it has been reported that the neuritis in co-infected people can be more severe and the reversal reaction may be more frequent after therapy.…”
Section: Hansen's Disease and Pregnancy 2021mentioning
confidence: 95%
“…It has been suggested that this may be due to the relatively low virulence of M. leprae or that HIV-infected individuals may die before leprosy (with its long incubation time) becomes clinically apparent (238). Nelson (286) has recently urged that investigators explore alternative explanations, however, since the apparent dissociation between the two diseases has continued even as the prevalence of AIDS has increased.…”
Section: Leprosy In Immunocompromised Individualsmentioning
confidence: 99%
“…Unlike tuberculosis, leprosy has not been observed to be more frequent in patients infected with human immunodeficiency virus (HIV) in regions where both diseases are endemic (162,238,303). It has been suggested that this may be due to the relatively low virulence of M. leprae or that HIV-infected individuals may die before leprosy (with its long incubation time) becomes clinically apparent (238).…”
Section: Leprosy In Immunocompromised Individualsmentioning
confidence: 99%
“…Surprisingly, the HIV infection has not affected the incidence/prevalence of leprosy. 11,12 This study comprised 40 cases of clinically diagnosed cutaneous tuberculosis and leprosy. The aim was to assess the usefulness of cytology, especially by applying the modified FNA technique, in diagnosing these diseases, by identifying characteristic cytological features.…”
mentioning
confidence: 99%